PENGARUH KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA MELALUI MOTIVASI KERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN BARRU - Zulkifli Aliah; Muhammad Idris; Muhammad Said (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2020)
The study aims to determine and analyze (1) the direct influence of competence and work environment on employee work motivation in the Barru Regency Public Works and Spatial Planning Office (2) the direct influence of competence and work environment on employee job satisfaction at the Barru Regency Public Works and Spatial Planning Office (3) the direct effect of work motivation on employee job satisfaction in the Barru District Public Works and Spatial Planning Office (4) The indirect effect of work competence and work environment on job satisfaction through employee work motivation at the Barru District Public Works and Spatial Planning Office. This research design uses survey research. The location of the research is the Public Works and Spatial Planning Office of Barru Regency. The study was conductedfrom October to November 2019. The population in this study included all employees of the Public Works and Spatial Planning Office in Barru Regency, amounting to 81 people. Sampling of this study was carried out using a saturated sampling technique (census), which determines the entire population to be sampled as many as 81 employees of th|e Barru District Public Works and Spatial Planning Department. The data analysis technique used is path analysis. The results showed that (1) there was a positive and significant direct effect on competence, work environment on work motivation towards employees at the Public Works and Spatial Planning Office in Barru District (2) there was a positive and significant direct effect on competence and work environment on employee job satisfaction in the Barru Regency Public Works and Spatial Planning Office (3) there is a positive and significant direct effect of work motivation on employee job satisfaction at the Barru District Public Works and Spatial Planning Office (4) there is a positive and significant effect on competence and work environment indirectly on job satisfaction through employee work motivation at the Barru District Public Works and Spatial Planning Office.